2012
DOI: 10.1088/0022-3727/45/39/395103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substrate and N content on the growth of the mid-infrared dilute nitride InAsN alloy

Abstract: We investigate the epitaxial growth of the dilute nitride InAsN alloy onto InAs and GaAs substrates with nitrogen content up to 1%. We report photoluminescence (PL) emission within the 2–4 µm spectral region and show that InAsN grown onto GaAs exhibits no degradation of the PL intensity and linewidth compared with epitaxial layers grown on near lattice-matched InAs substrates. Also, nitrogen can induce a significant reduction in the thermal quenching of the PL emission, which we attribute to the reduction in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Despite the presence of misfit and threading dislocations in all these layers, our optical studies indicate that In(AsN) grown onto GaAs exhibits little or no degradation of the photoluminescence properties compared with epitaxial layers grown on InAs, and that in both structures (i.e., In(AsN) on GaAs and InAs) the incorporation of nitrogen leads to comparable red shifts of the fundamental band gap. 11 Also, in stark contrast to other dilute nitride alloys, such as Ga(AsN), the electrical conductivity retains the characteristic features of transport through extended states with electron mobilities that remain relatively large even for [N] = 1% (μ e = 6 × 10 3 cm 2 V −1 s −1 at 300 K). 12 All wafers were processed into Hall bars of length L = 1250 μm and width W = 250 μm.…”
Section: Samples and Experimentsmentioning
confidence: 92%
See 1 more Smart Citation
“…Despite the presence of misfit and threading dislocations in all these layers, our optical studies indicate that In(AsN) grown onto GaAs exhibits little or no degradation of the photoluminescence properties compared with epitaxial layers grown on InAs, and that in both structures (i.e., In(AsN) on GaAs and InAs) the incorporation of nitrogen leads to comparable red shifts of the fundamental band gap. 11 Also, in stark contrast to other dilute nitride alloys, such as Ga(AsN), the electrical conductivity retains the characteristic features of transport through extended states with electron mobilities that remain relatively large even for [N] = 1% (μ e = 6 × 10 3 cm 2 V −1 s −1 at 300 K). 12 All wafers were processed into Hall bars of length L = 1250 μm and width W = 250 μm.…”
Section: Samples and Experimentsmentioning
confidence: 92%
“…29,30 Monte Carlo simulations of the electron dynamics have revealed that linear magnetoresistance can arise from multiple scattering of the current-carrying electrons by low-mobility islands within the conducting layer. 29 Since our InAs and In(AsN) epilayers are grown on highly lattice-mismatched GaAs, threading dislocations tend to form at the epilayer/substrate interface 11 and are likely to cause local macroscopic (> 0.1 μm) variations in the electron mobility. In particular, the strength of the linear magnetoresistance depends on the island-coverage factor f according to a simple relation, i.e., R xx /R xx = 0.5f (1 − f ) −1 μ e B z .…”
Section: B Electron Mass Mobility and Scattering Timementioning
confidence: 99%
“…Growth details have been reported elsewhere. [41] The samples were irradiated using a low energy (100 eV) Kaufman source (with ion current densities of a few µAcm -2 and H doses varying from dH=0.5×10 16 to 80×10 16 ionscm -2 ) to minimize possible damage due to the impinging H ions. During the hydrogenation process, hydrogen diffusion into the sample was promoted by heating the samples at temperatures (TH) ranging from 250 °C to 375 °C.…”
Section: Methodsmentioning
confidence: 99%
“…For almost all the samples the [N] content determined by PL was found to be in good agreement with the nominal value as determined by x ray diffraction. Growth details have been reported elsewhere [41]. The samples were irradiated using a low energy (100 eV) Kaufman source (with ion current densities of a few μA cm −2 and H doses varying from d H =0.5×10 16 to 80×10 16 ions•cm −2 ) to minimize possible sample damage due to the impinging H ions.…”
Section: Methodsmentioning
confidence: 99%
“…In In(Ga)As 1−x N x alloys, it has been and still is quite challenging to obtain accurate knowledge of alloy composition x, the site selectivity of n-and/or p-type dopants, and the bonding of N with its neighboring In(Ga) atoms, i.e., "N-In(Ga)" [11][12][13][14][15][16]. From a practical perspective, it is equally stimulating to obtain the correct thickness-dependent structural, electronic and phonon characteristics of III-V-N alloys, MQWs and SLs [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%